PERANCANGAN PERHIASAN MODERN UNTUK MEMPERKENALKAN TRADISI “TELINGAAN ARUU” KHAS SUKU DAYAK - Theresia Firstianti Santoso; Gunawan Gunawan; Kumara Sadana Putra (CALYPTRA, 2018)
Dayak tribe is one of the tribes contained in Borneo which has a very distinctive "Telingaan Aruu" culture. The tradition is a tradition passed on from generation to generation to Dayak’swomen. However, this tradition has begun to be abandoned because of the assumption that the tradition is outdated. Therefore, there should be an introduction of the culture to the general public, so that the younger generation still know the existence of the tradition in Indonesia. Currently, women often use jewelry every day to complement the appearance and increase confidence. In addition, based on a data found, the export sales of Indonesian jewelry has also increased in the last five years. This is what opens up opportunities for custom made jewelry with today's societythat is modern jewelry with no leaving the elements of Indonesian culture, especially the Dayak tribe. To realize the idea, then conducted interviews, observations, and research for the consideration of making the design until the realization of products and marketing. The products are made from silver and consists of several types of jewelry, that isbracelets, necklaces, brooches, headpiece, and earrings.